Computational modelling of belt of tire-casing - Krmela, Jan; Krmelová, Vladimíra (Latvia University of Afgriculture, 2019)
The paper is focused on computational modelling of composites with elastomeric matrix and steel or textile cords, such as belts of tire casings for passenger cars. The main attention is paid to creation of computational models of the steel-cord belt and textile carcass. The sidewall of a tire casing shows the material of cords and number of plies in the sidewall and under the tread of the tire casing. Normally, the sidewall consists of one or two polyester plies and in the tread there are, e.g. four plies: one polyester ply, two steel-cord plies and one polyamide ply. The Finite Element Method using the program system ANSYS is applied to the computational modelling. In relation to the computational modelling of stress-strain analyses for belts of tire casing, it is necessary to pay attention to the materials as well as the geometric input data aspect in order to make precise output results. The SOLID186 element type and Mooney-Rivlin material parameters for elastomer are used. The geometric parameters are obtained by an image analysis of the cross-section of the tire casing. For validation, the experimental data from tensile and bend tests are used. The results from computational modelling provide better understanding of the mechanical properties of composites with steel or textile reinforcements. The obtained outputs of computational modelling of belts can be used for geometry and cordsituate optimization (angle of reinforcement). The purpose of the optimization is to obtain characteristics (stiffness parameters in individual directions) of belts for predicting deformation behaviour of a tire.
Výpočtové modelování nárazníku pláště pneumatiky
Keywords: tire casing; elastomer; Mooney-Rivlin; FEM; ANSYS; plášť pneumatiky; elastomer; Mooney-Rivlin; MKP; ANSYS